The pH of a solution is a measure of how acidic it is. The greater the acidity, the lower the pH. The function f(x) = −log x gives the pH of a solution, where x is the concentration of hydrogen ions, in moles per liter.

The graph of f(x) = −log x is________________of the graph of g(x)=log x

answer options:

a: vertical translation (not correct answer)
b: horizontal translation
c: reflection in the x-axis
d: reflection in the y-axis

Answers

Answer 1

Answer:

c. a reflection in the x-axis.

Step-by-step explanation:

All values of log x are made  negative by the transformation so it is a reflection in the x axis.

Answer 2

The graph of [tex]f(x) =-log x[/tex] is the reflection in the x-axis of the graph of [tex]g(x)=log x[/tex].

What is a graph?

" Graph is defined as a pictorial representation of the relation between the variables in the coordinate plane along x-axis and y-axis."

According to the question,

Given function on the graph,

[tex]f(x) =-log x[/tex]

[tex]g(x)=log x[/tex]

[tex]'x'[/tex] represents the concentration of hydrogen ions, in moles per liter.

value of [tex]'x'[/tex] remain the same in both cases.

[tex]f(x)[/tex] value is negative.

[tex]g(x)[/tex] value is positive.

The graph of [tex]f(x)[/tex] lying in the first quadrant and the graph of  [tex]g(x)[/tex] lying in the fourth quadrant.

Therefore, the graph of [tex]f(x)[/tex] is the reflection in the x-axis of the graph of [tex]g(x)[/tex].

Hence, Option(C) is the correct answer.

Learn more about graphs here

https://brainly.com/question/20381610

#SPJ2


Related Questions


9 is 0.32% of what number?​

Answers

Answer:

2812.5

Step-by-step explanation:

Is means equals and of means multiply

9 = .32% * W

Change the percent to a decimal

9 = .0032 * W

Divide each side by .0032

9/.0032 = .0032W/.0032

2812.5 = W

The number is 2812.5

Answer:

2,812.5

Step-by-step explanation:

Evaluate -x+4x when x=-2

Answers

Use the substitution method

-x+4x  when x=-2

-(-2)+4(-2)  Positive number * ( multiplying)Negative number=Negative number

2-8

=-6

Answer is -6

The answer is -6. The explanation is shown in the picture.

what is the slope of the line and y intercept of y = x + 1

Answers

Answer:

The slope and y-intercept are both [tex]\bf{1}[/tex].

Explanation:

This equation is written in slope-intercept form, or [tex]y=mx+b[/tex], where [tex]m[/tex] is the slope and [tex]b[/tex] is the y-intercept.

Since there is no coefficient to [tex]x[/tex], which would have been [tex]m[/tex], [tex]m=1[/tex], so the slope is [tex]1[/tex].

[tex]b=1[/tex], so the y-intercept is also [tex]1[/tex].

Consider kite WXYZ.

What are the values of a and b?
a = 4; b = 10
a = 4; b = 40
a = 8; b = 10
a = 8; b = 40

Answers

Answer:

a = 8 ; b = 40

I just took the test and I got it right

Answer:

D

Step-by-step explanation:

D on edge :)

Solve the given inequality. If necessary, round to four decimal places.


134a < 19
Question 4 options:

a < 0.287

a < 4.2641

a < 1.3863

a < 2.5649

Answers

Answer:

[tex]a < 0.287[/tex]

Step-by-step explanation:

we have

[tex]13^{4a} < 19[/tex]

Solve for a

Apply log both sides

[tex]log(13^{4a}) < log(19)[/tex]  

Remember the rule

㏒(a^n) = n ㏒(a)

so

[tex](4a)log(13) < log(19)[/tex]

Divide by 4 log(13) both sides

[tex]a < log(19)/[4log(13)][/tex]

[tex]a < 0.2870[/tex]

f(x) = x^2 - 5

g(x) = 4x - 4

Find (f-g) (5)

4

-5

-4

5

Answers

Answer:

The correct answer option is: 4.

Step-by-step explanation:

We are given the following two functions and we are to find the value of [tex] ( f - g ) ( 5 ) [/tex]:

[tex]f(x) = x^2 - 5[/tex]

[tex]g(x) = 4x - 4[/tex]

Finding [tex] ( f - g ) ( x ) [/tex]:

[tex] ( f - g ) ( x ) [/tex] [tex]= (x^2-5)-(4x-4) = x^2-4x-5+4[/tex]

[tex]( f - g ) ( x ) = x^2-4x-1[/tex]

So, [tex]( f - g ) ( 5 ) = (5)^2-4(5)-1 = 4[/tex]

Answer:

4

Step-by-step explanation:

f(x) = x^2 - 5

g(x) = 4x - 4

(f-g) (x)= x^2 - 5   - (4x - 4)

Distribute the minus sign

           = x^2 - 5   - 4x + 4

          = x^2 -4x-1

Let x = 5

(f-g) (5) = 5^2 -4(5) -1

            =25 - 20 -1

             =5-1

              =4

if a + b + C = -1 and x + y + z = -8, what is -8z -8x + 5a + 5c - 8y + 5b

Answers

Answer:

59

Step-by-step explanation:

a + b + C = -1

x + y + z = -8

We want 5a so multiply the first equation by 5

5(a + b + c) = -1*5

5a+5b+5c = -5

We want -8x so multiply the second equation by -8

-8(x + y + z) = -8*-8

-8x-8y-8x = 64

Add these equations together

5a+5b+5c = -5

-8x-8y-8x = 64

---------------------------

-8x -8y-8x+5a+5b+5c = 59

Rearrange the order

-8z -8x + 5a + 5c - 8y + 5b = 59

Answer:

59

Step-by-step explanation:

The first step here is to rewrite -8z -8x + 5a + 5c - 8y + 5b as

                                                    -8x - 8y - 8z + 5a + 5b + 5c.

This is the same as -8(x + y + z) + 5(a + b + c).

Subbing -8 for (x + y + z) and -1 for (a + b + c), we get -8(-8) - 5, or 59.

Write quadratic equation whose roots are 1 and -3 and whose leading coefficient is 4

Answers

Answer:

4x^2 + 8x - 12 = 0.

Step-by-step explanation:

We first write it in factor form.

4(x - 1)(x + 3) = 0

4(x^2 + 2x - 3) = 0

4x^2 + 8x - 12 = 0 (answer).

Answer:

4x^2 + 8x - 12 = 0

Step-by-step explanation:

A quadratic equation with roots a and b has the equation (x - a)(x - b) = 0.

You roots are 1 and -3.

The equation is

(x - 1)(x - (3)) = 0

(x - 1)(x + 3) = 0

We can multiply it out.

x^2 + 3x - x - 3 = 0

x^2 + 2x - 3 = 0

Since we need the leading coefficient to be 4, we multiply both sides by 4.

4x^2 + 8x - 12 = 0

A triangle has vertices at L(2, 2), M(4,4), and N(1,6). The
Triangle is transformed according to the rule Ro 180°
Which statements are true regarding the
transformation? Select three options.
.
The rule for the transformation is (x, y) + (-X, -Y).
The coordinates of L'are (-2,-2).
The coordinates of M' are (4,4).
The coordinates of N' are (6,-1).
The coordinates of N' are (-1,-6).

Answers

Answer:

The rule for the transformation is (x, y) + (-X, -Y)

The coordinates of L'are (-2,-2).

The coordinates of N' are (-1,-6)

Step-by-step explanation:

90 degree rotation from (x,y) results in (-x, y) and 180 degree results in (-x,-y)

The coordinates will change accordingly

L(2,2) will become L'(-2,-2)

M(4,4) will become M'(-4,-4)

and

N(1,6) will become N'(-1,-6)

So the correct statements are:

The rule for the transformation is (x, y) + (-X, -Y)

The coordinates of L'are (-2,-2).

The coordinates of N' are (-1,-6) ..

The true options are:

The rule of transformation is [tex](x, y) \to (-x, -y)[/tex]The coordinates of L'are (-2,-2).The coordinates of N' are (-1,-6)

The vertices of the triangle are given as:

L(2, 2), M(4,4), and N(1,6).

The rule of transformation is Ro 180°.

This is represented as:

[tex](x, y) \to (-x, -y)[/tex]

So, we have:

[tex]L' = (-2,-2)[/tex]

[tex]M' = (-4,-4)[/tex]

[tex]N' = (-1,-6)[/tex]

Hence, the true options are (a), (b) and (e)

Read more about transformation at:

https://brainly.com/question/4289712

What is the following simplified product? Assume x>/= 0

Answers

Answer: second option.

Step-by-step explanation:

We know that:

[tex]\sqrt[n]{a^n}=a[/tex]

[tex](a^m)(a^n)=a^{(m+n)[/tex]

Then we can simplify the radicals:

[tex]2\sqrt{8x^3}(3\sqrt{10x^4}-x\sqrt{5x^2})=(2\sqrt{2^2*2*x^2*x})(3\sqrt{10x^4}-x\sqrt{5x^2})=\\\\=2*2*x\sqrt{2x}=3x^2\sqrt{10}-x*x\sqrt{5}\\\\=4x\sqrt{2x}(3x^2\sqrt{10}-x^2\sqrt{5})[/tex]

Since:

[tex](a\sqrt[n]{x})*(b\sqrt[n]{y})=ab\sqrt[n]{xy}[/tex]

We can apply Distributive property:

[tex]4x\sqrt{2x}(3x^2\sqrt{10}-x^2\sqrt{5})\\\\12x^3\sqrt{20x}-4x^3\sqrt{10x}[/tex]

Simplifying:

[tex]12x^3*2\sqrt{5x}-4x^3\sqrt{10x}\\\\24x^3\sqrt{5x}-4x^3\sqrt{10x}[/tex]

Answer:

B

Step-by-step explanation:

edg2021

Samantha’s rectangular gift is 10 inches. by 12 inches and is framed with a ribbon. She wants to use the same length of ribbon to frame a circular clock. What is the maximum radius of the circular clock? Round to the nearest whole number.
(JUSTIFY)

Answers

Answer:

7 inches

Step-by-step explanation:

The dimension of the rectangular gift is 10 by 12 inches so let us find the perimeter of this rectangle.

Perimeter of rectangular gift = 2 (L+ W) = 2 (10 +12) = 44 inches

Since we are to use the same length of ribbon to wrap a circular clock so the perimeter or circumference of the clock should be no more than 44 inches.

[tex]2\pi r=44[/tex]

[tex]r=\frac{44}{2\pi }[/tex]

[tex]r=7.003[/tex]

Therefore, the maximum radius of the circular clock is 7 inches.

Answer:

= 7 inches

Step-by-step explanation:

The ribbon covers the perimeter of the gift.

Perimeter of a rectangle= 2L+2W

=2(12)+2(10)

=44 inches

If the same ribbon is used to frame a circular clock, the perimeter remains to be 44 inches.

Perimeter of a circle= 2πr where r is the radius of the circle.

44 inches= 2×π×r

r=44/2π

=7.0 inches

Radius of the circular clock is 7 inches

How would I solve for y?

Answers

Answer:

y=40

Step-by-step explanation:

Step 1: Add 1 to both sides.

3y−1+1=119+1

3y=120

Step 2: Divide both sides by 3.

3y /3  =  120 /3

y=40

Try this trick out on a friend. Tell your friend to place a dime in one hand and a penny in the other hand. Explain that you can determine which hand is holding the penny.

Here’s how to do it:

a. Ask the friend to multiply the value of the coin in his or her RIGHT hand by 4, 6, or 8 and then to multiply the value of the coin in his or her LEFT hand by 3, 5, or 7.
b. Now ask the friend to add the two results together and tell you the total.
c. If the total is EVEN, the penny is in the RIGHT hand. If the total is ODD, the penny is in the left hand.

Answers

Final answer:

The math trick described allows you to figure out which hand a friend is holding a penny in by having them multiply the value of the coins in their hands by specific numbers, adding the results, and determining whether the total is even or odd.

Explanation:

The subject at hand pertains to a mathematical trick used to determine in which writing a friend is holding a penny. To execute the scheme, follow the procedure:

Ask your friend to multiply the coin's value in their right hand by 4, 6, or 8. Then, instruct them to bear the coin's weight in their left hand by 3, 5, or 7.Next, ask them to add the two results and the total.the penny is in the friend's right hand if the total is even. If the sum is odd, the penny is in their left hand. Here's why: When a dime (10 cents) is multiplied by any integer, the result will be an even number. But a penny (1 cent) multiplied by any number will keep its parity (odd or even). So, if the total sum is weird, the left-hand number, odd, must have been contributed by the penny.

Learn more about math tricks here:

https://brainly.com/question/2273245

#SPJ3

How do u do this please help!!

Answers

Answer:

C. 3 gal. 3 qt. 1 pt.

Step-by-step explanation:

1 gallon = 4 quarts

5 gallons 2 quarts 1 pint = 4 gallons 6 quarts 1 pint

(5 gallons 2 quarts 1 pint) - (1 gallon 3 quarts)

= (4 gallons 6 quarts 1 pint) - (1 gallon 3 quarts)

= 3 gallons 3 quarts 1 pint

PLEASE HURRY
WILL GIVE BRAINLIEST

Answers

Answer:

1 and 4

Step-by-step explanation:

There are 2 shaded, and 2 even numbers

There are 2 unshaded, and 2 odd numbers.

Hope this helps

If f(x) = 4 – x2 and g(x) = 6x, which expression is equivalent to (g – f)(3)?

Answers

Answer:

6(3) - (4 - 3²) = 6(3) - 4 + 3²

Step-by-step explanation:

[tex]f(x)=4-x^2,\ g(x)=6x\\\\(g-f)(x)=g(x)-f(x)\\\\(g-f)(x)=6x-(4-x^2)\\\\(g-f)(3)-\text{put x = 3 to the equation}\\\\(g-f)(3)=6(3)-(4-3^2)[/tex]

If you bought a stock for $45 dollars and could sell it fifteen years later for three times what you originally paid. What was your return on owning this stock?

Answers

Answer:

90$

Step-by-step explanation:

45$

45*3=135

But your return was 3 times the price, so subtract a 45.

135-45=90$

Answer: $90

Step-by-step explanation:

Given : The cost of one stock = $45

And the value of that stock after 15 years is 3 times the paid price.

i.e. The value of that stock after 15 years = [tex]3\times45=\$135[/tex]

Then, the return on owning this stock = [tex]\text{Value after 15 years -Paid price}[/tex]

[tex]=\$135-\$45=\$90[/tex]

Therefore, the return on owning this stock = $90

The appropriate translation of the phrase 11 more than 20 percent of a number is:

0.2n+11

True or false?

Answers

Answer: True

Step-by-step explanation: 20% can also be written as 0.2 and if you know the number then you would multiply it by 0.2, then if you needed to add 11 that is exactly how you would write that equation

Find the value of X in the picture

Answers

Answer:

The measure of the arc x is 80°

Step-by-step explanation:

we know that

The semi-inscribed angle is half that of the arc it comprises

so

40°=(1/2)[arc x]

solve for x

arc x=(2)(40°)=80°

Find the value of x if A, B, and C are collinear points and B is between A and C.
AB=x,BC=x+2,AC=14
A. 6
B. 10
C. 9
D. 5

Answers

When A, B, and C are collinear points and B is between A and C, value of AB(x) is 6. Therefore, option A is the correct answer.

If we know that points A, B, and C are collinear, with B between A and C, then we can use the given distances AB and BC to find the total distance AC.

Since AB is given as x, and BC as x+2, and we know AC is the sum of AB and BC< which is equal to 14, we can set up the equation:

AB + BC = AC

x + (x+2) = 14

Combining like terms gives us:

2x + 2 = 14

Subtracting 2 from both sides of the equation, we have:

2x = 12

Dividing both sides by 2 to isolate x:

x = 6

Therefore, the length of segment AB, which is x, is 6 units. Option A. 6 is the correct answer.

What is the slope of the line given by the equation below?
y = 4x-2

Answers

Answer:

slope: 4

Step-by-step explanation:

y = 4x-2 is in the form y = mx +b where m is the slope and b is the y intercept

4 is the slope and -2 is the y intercept

Answer:

4

Step-by-step explanation:

The slope-intercept form of an equation of a line:

[tex]y=mx+b[/tex]

m - slope

b - y-intercept

We have [tex]y=4x-2[/tex].

Therefore

the slope [tex]m=4[/tex]

the y-intercept [tex]b=-2[/tex]

what is a reasonable estimate for the problem? 3 3/4 x -2/5

Answers

Answer:

You can not break that down any further if x does not equal anything and the equation is not equal to anything.

Step-by-step explanation:

-1.5

By using a calculator, making the mixed numeral 3 3/4=3.75, and making -2/5 a decimal = -0.4, you can now simply multiply:

3.75 x -0.4= -1.5
Remember that a positive and a negative give you a negative answer.

which statement must be true about the diagram?

Answers

Answer:

It's the third choice.

Step-by-step explanation:

M < NKM and m < MKL both equal  61 degrees

so KM is a bisector of < NKL.

Answer:

C:ray MK is an angle bisector of angle NKL

Step-by-step explanation:

We have to find the true statement about the diagram

[tex]\angle JKN=58^{\circ}[/tex]

[tex]\angle NKM=61^{\circ}[/tex]

[tex]\angle MKL=61^{\circ}[/tex]

[tex]\angle NKM=\angle MKL=61^{\circ}[/tex]

When a ray is a bisector of any angle then the angles are equal which are made by bisection of the angle.

By using this definition

The ray MK is a bisector of angle NKL because angle NKM and MKL are equal.

Answer:C

pls help solve this problem

Answers

Answer:

  166 mm²

Step-by-step explanation:

The area is given by ...

  A = (1/2)Pa . . . . . where P is the perimeter and "a" is the apothem

One side of a 6-sided figure is shown as 8 mm, so the perimeter is ...

  P = 6·(8 mm) = 48 mm

Filling in the apothem value, we have ...

  A = (1/2)(48 mm)(4√3 mm) = 96√3 mm² ≈ 166 mm²

The area of the hexagon is about 166 mm².

If sinx= sqrt(3)/2, and 90° < x < 180°, what is cos(x/2)?

Answers

Answer:

cos 60° = 1/2

Step-by-step explanation:

* Lets explain how to solve the question

- If angle Ф lies in the first quadrant then sin Ф , cos Ф and tan Ф

 are positive values

- The equivalent angle of angle Ф in the second quadrant is 180° - Ф

 and sin Ф is positive but cos Ф and tan Ф are negative

- The equivalent angle of angle Ф in the third quadrant is 180° + Ф

 and tan Ф is positive but cos Ф and sin Ф are negative

- The equivalent angle of angle Ф in the fourth quadrant is 360° - Ф

 and cos Ф is positive but sin Ф and tan Ф are negative

* Lets solve the problem

sin x = √3/2

90° < x < 180°

∴ ∠ x lies in the second quadrant

m∠ x = 180° - Ф

- Let sin Ф = √3/2

∴ Ф = sin^-1 (√3/2)

Ф = 60°

∵ x = 180° - Ф

∴ x = 180° - 60°

x = 120°

- To find cos(x/2) divide 120° by 2

∵ cos (120°/2) = cos (60°)

cos 60° = 1/2

What is the slope of the line containing (6, -7) and (5, -9)?
A) 1
B) -2.
C) 2
D) 16

Answers

Answer: C

Step-by-step explanation:

y2-y1/x2-x1

-9+7/5-6 = 2

Which expression are equivalent to the one below? Check all that apply. Log5 5+log5 125

Answers

Answer:

B. 4

C. Log₅ 625

Step-by-step explanation:

When given the sum of two logarithms to the same base, let us say

LogₐB +LogₐC, Then, the sum is equivalent to Logₐ(B×C)

=Logₐ BC

The sum given in the question is Log₅5 + Log₅125

This is equivalent to Log₅(5×125)=Log₅625

Log₅625=4 (Since 625=5⁴, the log of 625 to base 5 is 4)

Answer:4 Log5 625 Log5(5^4)

Step-by-step explanation:

What’s the surface area of a regular pyramid if the base is 7 and the height is 10

Answers

Answer:

Step-by-step explanation:

the base is a square, and then there are four triangles that meet at their tip.

so you need to find the area of the base, and the four triangles.

base-l*w=7*7=49

triangles=1/2*b*h*4=1/2*7*10*4=35*4=140

140+49=189

Final answer:

The surface area of a regular pyramid with a square base of 7 units and a height of 10 units is approximately 197.26 square units. This is calculated by adding the area of the square base to the combined area of the four triangular faces.

Explanation:

To find the surface area of a regular pyramid with a square base, we need to calculate the area of the square base and the area of the four triangular faces. The formula for the area of a square is base x base. If the base is 7 (units unspecified, but assumed to be the same for both height and base), the area of the base is 7 x 7 = 49 square units. To find the area of a triangular face, we use the formula 1/2 x base x slant height.

To calculate the slant height, we need the half of the base of the triangle (which is 3.5 if the base of the square is 7), and the given perpendicular height of the pyramid, in this case, 10 units. We can use the Pythagorean theorem to find the slant height. The slant height (s) can be calculated as s = \\sqrt{(3.5)² + 10²} = \\sqrt{12.25 + 100} = \\sqrt{112.25}, which is approximately 10.59 units.

The area of one triangular face is 1/2 x 7 x 10.59 ≈ 37.065 square units. There are four triangular faces, so their total area is 37.065 x 4 ≈ 148.26 square units. Thus, the total surface area of the pyramid is the sum of the area of the base and the four triangular faces: 49 + 148.26 ≈ 197.26 square units.

/5×+4/ =/×+9/ solve for x​

Answers

Answer:

[tex]\large\boxed{x=\dfrac{5}{4}\ \vee\ x=-\dfrac{13}{6}}[/tex]

Step-by-step explanation:

[tex]|5x+4|=|x+9|\iff5x+4=x+9\ or\ 5x+4=-(x+9)\\\\5x+4=x+9\qquad\text{subtract 4 from both sides}\\5x=x+5\qquad\text{subtract x from both sides}\\4x=5\qquad\text{divide both sides by 4}\\x=\dfrac{5}{4}\\\\5x+4=-(x+9)\\5x+4=-x-9\qquad\text{subtract 4 from both sides}\\5x=-x-13\qquad\text{add x to both sides}\\6x=-13\qquad\text{divide both sides by 6}\\x=-\dfrac{13}{6}[/tex]

Solve the system of equations given below.
8x + 4y = 16
7y = 15
-
1
OA. (4,-2)
B. (-2,4)
C. (1.2)
:
D.
(2,1)
Reset
Next
Next

Answers

Answer:

Step-by-step explanation:

we have the system :

8x+4y=16

7y=15

the easiest unknown to find first is y because we have the second equation contains only y :

7y=15   we divide both sides by 7 we get : y=[tex]\frac{15}{7}[/tex]

then we can substitute this value in the first equation to find x :

8x+4 [tex]\frac{15}{7}[/tex] = 16

means : 8x+[tex]\frac{60}{7}[/tex] = 16

8x=16-[tex]\frac{60}{7}[/tex]

8x = [tex]\frac{52}{7}[/tex]

divide both sides by 8 :

x = [tex]\frac{13}{14}[/tex]

so the solution is ([tex]\frac{13}{14}[/tex],[tex]\frac{15}{7}[/tex])

this is the solution of the system you submitted

Now if you meant this system :

8x+4y=16

7y=15-1    

we get :

7y=14   which gives us y=2

then 8x+4(2)=16   gives us : 8x+8=16

means 8x=8  

means x=1

and in this case the solution will be (1,2)  answer C

Other Questions
Complete the phylogenetic tree by matching each characteristic that arose during the evolution of animals to its correct position. ( Start from top to bottom boxes)OPTIONS:BackboneTissuesCoelomSegmentationEndoskeleton The celsius and Fahrenheit scales are related by the equation C=5/9(f-32). What temperature fahrenheit would give a temperature of 5C? four less than the quotient of a number cubed and seven, increased by three You have$560 in an account which pays 4.8% compounded annually. If you invest your money for 8 years, then how many dollars of interest will you earn by the end of term You are hiking and are trying to determine how far away the nearest cabin is, which happens to be due north from your current position. Your friend walks 200 yards due west from your position and takes a bearing on the cabin of N 30.7E. How far are you from the cabin? What element of caravaggio's painting style was the subject of criticism and occasionally seen deemed inconsistent with the artistic guidelines established by the council of trent? 4. A student is chosen at random from the student body at a given high school. The probability that thestudent selects Math as the favorite subject is 1/4. The probability that the student chosen is a junior is116/459. If the probability that the student selected is a junior or that the student chooses Math as thefavorite subject is 47/108, what is the exact probability that the student selected is a junior whosefavorite subject is Math? Explain why there would be more errors in dna replication if thymine was sometimes able to form bonds with cytosine. PLEASE HELP one positive integer is 7 less than another. The product of two integers is 44. what are the integers? Find the distance between the points (-3, 2) and (4, -5) Please help will give the brainliest Find the coordinates of the vertices formed by the system of inequalities. X 3 -x + 3y 12 4x + 3y 12 A (0, 3), (4, 0), (5, 3) B (3, 0), (0, 4), (3, 5)C (-3, 3), (1, 3), (0, 4) D (3, -3), (3, 1), (4, 0)2. At What point is the maximum value found in the system of inequalities graphed below for the function f(x, y) = x - 2y?A (0, 3)B (0, 0)C (5, 0)D (5, 3) Tubular ___________ occurs when certain substances (i.e. iions, drugs) are removed from the bloodstream and placed back into the renal tubule.a. Eliminationb. Reabsorptionc. Secretiond. Filtration 2. In 1973, Secretariat set the current record of 1 minute 59.40 seconds for the Kentucky Derby. The length of this race is 10 furlongs1 furlong1/8 mile). What was Secretariat's average speed in this race in mi/hr? 19. Solve sin O+ 1 = cos 20 on the interval 0x < 2xpi How many atoms of carbon are combined to with 2.81 moles of hydrogen atoms in a sample of the compound ethane, C2H6? What is the 20th digit after the decimal point of the sum of the decimal equivalents for the fractions 1/7 and 1/3? Two long conducting cylindrical shells are coaxial and have radii of 20 mm and 80 mm. The electric potential of the inner conductor, with respect to the outer conductor, is +600 V. An electron is released from rest at the surface of the outer conductor. What is the speed of the electron as it reaches the inner conductor? P is a prime number and q is a positive integers such that p + q = 1696 IF P and Q are co primes and their Lcm is 21879 Then find p and q Which of the following is true about organizing items and information during scientific investigations?A.Items and information must be organized differently each time an investigation is repeated.B. No two investigations can use the same method for organizing items and information.There is only one method for organizing items and information in a scientific investigation.WEThere are usually multiple methods for organizing items and information in a scientific investigation. Use the tables to determine which function will eventually exceed the other, and provide your reasoning. xf(x)15 06 15 22 xg(x)10.166 0 1 1 6 2 36 f(x) will eventually exceed g(x) because f(x) is an exponential function. f(x) will eventually exceed g(x) because f(x) has a higher rate of change. g(x) will eventually exceed f(x) because g(x) is an exponential function. g(x) will eventually exceed f(x) because g(x) has a higher rate of change.